Decoding physiological and pathological roles of innate immune cells in eye diseases: the perspectives from single-cell RNA sequencing - Lu, Chen; Mao, Xiying; Yuan, Songtao (Frontiers in Immunology, 2024)
Single-cell RNA sequencing (scRNA-seq) has facilitated a deeper comprehension of the molecular mechanisms behind eye diseases and has prompted the selection of precise therapeutic targets via examining the cellular and molecular intricacies at the single-cell level. This review delineates the pivotal role of scRNA-seq in elucidating the functions of innate immune cells within the context of ocular pathologies. Recent advancements in scRNA-seq have revealed that innate immune cells, both from the periphery and resident in retina, are actively engaged in various stages of multiple eye diseases. Notably, resident microglia and infiltrating neutrophils exhibit swift responses during the initial phase of injury, while peripheral monocyte-derived macrophages exhibit transcriptomic profiles akin to those of activated microglia, suggesting their potential for long-term residence within the retina. The scRNA-seq analyses have underscored the cellular heterogeneity and gene expression alterations within innate immune cells, which, while sharing commonalities, exhibit disease-specific variations. These insights have not only broadened our understanding of the cellular and molecular mechanisms in eye diseases but also paved the way for the identification of candidate targets for targeted therapeutic interventions. The application of scRNA-seq technology has heralded a new era in the study of ocular pathologies, enabling a more detailed appreciation of the roles innate immune cells play across a spectrum of eye diseases.